Die skuldgebed in Esra 9:6-15 - Venter, Pieter M. (HTS teologiese studies, 2005)
The penitential prayer in Ezra 9:6-15The penitential prayer is a traditional Gattung used in ancient Israel. The prayer of Ezra 9:6-15 bears all the characteristic marks of this genre. In this prayer a historical scheme and themes such as “the land” are used to depict the Judean community’s sin. In a study of its literary structure, macro narrative context and socio historic background, this article shows that the confession in the prayer in reality is a liturgical strategy to proclaim Yahweh’s righteousness in his relationship with his people. Rather than imploring God, the community of faith expresses its belief in God and their identity as God’s own people in this prayer.